Analysis on goal scoring patterns by Malaysia U-20 futsal team in AFC U-20 futsal championship Thailand 2017 / Muhammad Afkar Mohd Sabri - Mohd Sabri, Muhammad Afkar (Faculty of Sport Science and Recreation, 2018)
This study was conducted in order to analyze goal scoring patterns by Malaysia U-20 Futsal Team in AFC U-20 Futsal Championship Thailand 2017. Five matches by Malaysia U-20 futsal team were selected to observe. The indictors included for this analysis are the goal scoring time, goalpost areas, scorer positions, parts of body used to score goal and the set play of goals scored. The data were collected through observational study and used of hand notational analysis. Chi Square Test was used to see the significant of this study. Most of the result shows that there were no significance different for the variables. The results of this study should not only give coaches a fresh insight into how to create more effective tactical plans, it also provides useful information on the characteristics of goal scoring patterns in futsal matches.